2019
DOI: 10.3390/rs12010003
|View full text |Cite
|
Sign up to set email alerts
|

Forest and Land Fires Are Mainly Associated with Deforestation in Riau Province, Indonesia

Abstract: Indonesia has experienced extensive land-cover change and frequent vegetation and land fires in the past few decades. We combined a new land-cover dataset with satellite data on the timing and location of fires to make the first detailed assessment of the association of fire with specific land-cover transitions in Riau, Sumatra. During 1990 to 2017, secondary peat swamp forest declined in area from 40,000 to 10,000 km 2 and plantations (including oil palm) increased from around 10,000 to 40,000 km 2 . The domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 41 publications
1
39
0
3
Order By: Relevance
“…Humid tropical forests are generally resistant to burning, but the transition from primary to secondary forests, shrubs, pastures, and agricultural plantations increases the frequency of fires (da Silva et al 2018;Adrianto et al 2020). Not only natural wildfires but also intentional burning to remove weeds for agriculture may trigger extensive fires.…”
Section: Wildfire and Intentional Burningmentioning
confidence: 99%
“…Humid tropical forests are generally resistant to burning, but the transition from primary to secondary forests, shrubs, pastures, and agricultural plantations increases the frequency of fires (da Silva et al 2018;Adrianto et al 2020). Not only natural wildfires but also intentional burning to remove weeds for agriculture may trigger extensive fires.…”
Section: Wildfire and Intentional Burningmentioning
confidence: 99%
“…Short-lived local fires can also occur out of these periods [10] [11]. In Indonesia, fires were detected in rubber, wood fiber and oil-palm plantations, forested areas and shrubland [10,11,68,69]. [10] reported that 16.6% of the fires detected between 2012 and 2015 on Sumatra and Kalimantan were located within legal agro-industrial oil-palm concessions.…”
Section: Impact Of Fire On Si Release From Topsoils and Littermentioning
confidence: 99%
“…[10] reported that 16.6% of the fires detected between 2012 and 2015 on Sumatra and Kalimantan were located within legal agro-industrial oil-palm concessions. Adrianto et al (2019) [69] showed that in Riau Province on Sumatra, Indonesia, most fires occur when forest or shrubland is converted to oil palm, wood fibre and logging plantations. They showed, that in regions that did not change land-cover a total area of 0.017 km 2 y −1 was affected by fire in plantations over the period 2002 -2016 compared to shrubland (0.067 km 2 y −1 ) and primary wet and dry forests (0.001 km 2 y −1 ) [69].…”
Section: Impact Of Fire On Si Release From Topsoils and Littermentioning
confidence: 99%
See 1 more Smart Citation
“…Another worrying fact is the degradation of forest-associated ecosystem, such as the peatland ecosystems of the Amazon, concentrated in Western and Central Amazon, mainly in Peru and Brazil (Román-Cuesta et al 2011, Lähteenoja et al 2012, Lähteenoja et al 2013, Draper et al 2014. Increased deforestation due to land use make these wet ecosystems susceptible to fire (Adrianto et al 2020). The peatlands comprise ecosystems that concentrate large amounts of carbon reserves, storing 1-8 PgC (1 Pg = 1 billion tons), in an area of approximately 35,000 km 2 (Lähteenoja et al 2012).…”
mentioning
confidence: 99%